The carceralist logic and the the struggle for rights - Bernuz Beneitez, María José (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2024)
In the last decade, it’s become apparent how some social groups, heterogenous among them, have asked for and celebrated longer prison sentences for crimes against the values they defend. The aim of this paper is to reflect on the paradox that some movements involved in the struggle for the consolidation of fundamental rights denounce the cruelty and dysfunctions generated by the penal system in general and prison in particular, but justify them as adequate means to make visible, respond to and resolve social problems. These inconsistencies can feed and increase the slippery slope towards punitive and prison exceptionalism and consolidate as another type of punitive populism.